2022
DOI: 10.1021/acs.jpca.2c01376
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark Ab Initio Characterization of the Abstraction and Substitution Pathways of the Cl + CH3CN Reaction

Abstract: We investigate the reaction pathways of the Cl + CH 3 CN system: hydrogen abstraction, methyl substitution, hydrogen substitution, and cyanide substitution, leading to HCl + CH 2 CN, ClCN/CNCl + CH 3 , ClCH 2 CN + H, and CH 3 Cl + CN, respectively. Hydrogen abstraction is exothermic and has a low barrier, whereas the other channels are endothermic with high barriers. The latter two can proceed via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…When the exothermic tautomerization of 1-MeCyt-Nπ · to the iminyl radical (1-MeCyt-Nσ · ) is taken into account, the N–H bond dissociation enthalpy decreases to ∼104 kcal/mol (DFT) and 103 kcal/mol (G4) kcal/mol (Figure S8) which are in agreement with previous results . Bond strengths of the C–H bonds in ACN and methanol are less than this. Thus, hydrogen atom abstraction from these organic cosolvents by dC· is exothermic, and these could be the sources of the hydrogen atom required for dC formation. Furthermore, dC· should be able to abstract hydrogen atoms from the 2′-deoxyribose backbone and thymine methyl group in DNA even more readily. , …”
Section: Results and Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…When the exothermic tautomerization of 1-MeCyt-Nπ · to the iminyl radical (1-MeCyt-Nσ · ) is taken into account, the N–H bond dissociation enthalpy decreases to ∼104 kcal/mol (DFT) and 103 kcal/mol (G4) kcal/mol (Figure S8) which are in agreement with previous results . Bond strengths of the C–H bonds in ACN and methanol are less than this. Thus, hydrogen atom abstraction from these organic cosolvents by dC· is exothermic, and these could be the sources of the hydrogen atom required for dC formation. Furthermore, dC· should be able to abstract hydrogen atoms from the 2′-deoxyribose backbone and thymine methyl group in DNA even more readily. , …”
Section: Results and Discussionsupporting
confidence: 89%
“…Consistent with previous work, the DFT calculations predict that the N–H bond dissociation enthalpy of the parent (1-MeCyt) to π-type aminyl radical (1-MeCyt-Nπ · ) is 107 kcal/mol, and the G4 level calculations agree with a value of 106 kcal/mol (Scheme and Figure S8). , …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What comes after the previous work on the title reaction? First, it is important to note that the previous computations only considered the H-abstraction channels, whereas our recent studies on the F/Cl/Br/I/OH + C2H6 20,21 and Cl + CH3NH2/CH3CN 22,23 reactions revealed several other channels such as hydrogen and methyl substitution for the reactions of C2H6 and the picture is even more complex in the cases of CH3NH2 and CH3CN. Thus, in the present study, we plan to characterize all the possible, chemically relevant pathways of the title reaction, thereby providing new qualitative insights into the mechanisms of the F + CH3NH2 process.…”
Section: Introductionmentioning
confidence: 96%